2014
DOI: 10.1097/01.pra.0000442937.61575.26
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Effect of Polypharmacy on the Hematologic Profiles of Clozapine Patients

Abstract: Autonomic agents, anti-infective agents, and proton pump inhibitors and other gastrointestinal agents were all associated with hematological ADRs when co-prescribed with clozapine. Medications from these classes should be initiated cautiously in patients being treated with clozapine to avoid precipitous drops in ANC or WBC that may increase the risk of agranulocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Carbamazepine should not be used in combination with clozapine, due to its potentiation of neutropenia and agranulocytosis . Anti‐infective agents, proton pump inhibitors and other gastrointestinal agents have also been associated with haematological adverse effects when co‐prescribed with clozapine . Non‐tricyclic antidepressants are rarely associated with agranulocytosis.…”
Section: Haematologic Diseasesmentioning
confidence: 99%
“…Carbamazepine should not be used in combination with clozapine, due to its potentiation of neutropenia and agranulocytosis . Anti‐infective agents, proton pump inhibitors and other gastrointestinal agents have also been associated with haematological adverse effects when co‐prescribed with clozapine . Non‐tricyclic antidepressants are rarely associated with agranulocytosis.…”
Section: Haematologic Diseasesmentioning
confidence: 99%
“…Clozapine combined with other antipsychotic agents has a synergistic effect on the risk of numerous side‐effects, including blood dyscrasias, diabetes mellitus, and pneumonia . Studies showed that clozapine recipients experienced more adverse drug reactions related to decreases in white blood cells or absolute neutrophil counts while using concomitant medications, including autonomic agents, anti‐infective agents, and gastrointestinal agents . Patients receiving clozapine combined with other antipsychotics had a higher risk of diabetes mellitus than patients not taking combination treatment .…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies showed that clozapine recipients experienced more adverse drug reactions related to decreases in white blood cells or absolute neutrophil counts while using concomitant medications, including autonomic agents, antiinfective agents, and gastrointestinal agents. 29,37 Patients receiving clozapine combined with other antipsychotics had a higher risk of diabetes mellitus than patients not taking combination treatment. 38 Additionally, clozapine combined with other antipsychotics resulted in a greater synergistic risk of pneumonia than clozapine monotherapy.…”
Section: Effect Of Clozapine Combination Therapy On Risk Of Tuberculosismentioning
confidence: 99%
“…It is known that clozapine can also develop the side effect of gastroesophageal reflux disease (GERD), the most common gastrointestinal complication associated with this drug [34]. PPIs, when usually coadministered with clozapine have a large drug-drug interaction in terms of hematological adverse reactions [35] demonstrated by a study [36] on 26 clozapine recipients with hematological adverse events, of which 96% were found to had taken PPI or ranitidine.…”
Section: Clozapinementioning
confidence: 99%
“…Omeprazole, a PPI, is a known agonist of the aryl hydorcarbon receptor (AHR) [36] that can increase the expression of the mRNA responsible for the synthesis of FM-O3 enzyme [37]. Flavin-containing monooxygenase (FM-O3) enzyme is present in leukocytes, known to assist in the generation of the nitrenium ion, a reactive oxygen species generated after further metabolism of clozapine metabolites-N-desmethylclozapine and clozapine N-oxide.…”
Section: Clozapinementioning
confidence: 99%